Consolidation and compression of deformable impregnated fibrous reinforcements: Experimental study and modeling of flow-induced deformations. (April 2020) - Hautefeuille, A.; Comas-Cardona, S.; Binetruy, C.
Abstract: Continuous fiber-reinforced thermoplastic composites can be produced by compression or consolidation processes at a temperature above the thermoplastic melting temperature. High production rates or high fluidity thermoplastic (TP-HF) viscosities can lead to large in-plane displacements of the fibrous network during the process. The same mechanisms appear when viscous toughened thermosets resins are used. One can assume that the in-plane displacements occur when the liquid thermoplastic flow sets the deformable fibrous reinforcement in motion. The composite material being manufactured is therefore subjected to a hydro-mechanical coupling between a liquid flow and a deformable continuous fibre reinforcement. Within this context, the in-plane flow-induced deformations during transverse consolidation are investigated in this study. An experimental setup is used in order to localize and quantify fibre tow displacements and large strains as a transient full-field measurement. Then, in order to identify the driving forces occurring during consolidation, these induced deformations are taken into account in the modeling. The fibrous reinforcement properties are redefined locally based on the measured full-field strains. The comparison of experimental and modeling results shows that the local in-plane drag force peaks mainly drive the onset of the fibrous architecture deformation.